Komunikasi Interpersonal Orang Tua Dalam Membentuk Perilaku Anak di Desa Sidomulyo Kecamatan Stabat Kab. Langkat - Br. Sitepu, Anisa Sukma Ningrum; Abdurrahman, Abdurrahman (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2024)
Communication is the most important part of human life, because humans are social creatures, to interact with other humans, both interpersonal and group communication. One of the communications that exist in the closest environment is the family. This research uses a qualitative approach method, which includes the collection and analysis of sufficient data to enable in-depth understanding based on a scientific foundation. This research was conducted in Sidomulyo Village, Stabat District, Langkat Regency, in April 2024. The research subjects consisted of both parents, who were selected based on specific cases related to communication between them. The results showed that differences in economic conditions have an impact on the way parents and children communicate in Sidomulyo Village. Positive albeit limited communication methods instill responsibility in children, while strict authoritative methods tend to result in aggressive behavior.